Rutting Prevention of Bituminous Mastic Using Microencapsulation Phase Change Material - Mizwar, I.K. (American Society of Civil Engineers (ASCE), 2021)
Rutting is a pavement degradation that can be alleviated by reducing temperature variations experienced by the pavement. These variations can be reduced by utilizing microencapsulated phase change material (MPCM). The objective of this study is to investigate the potential use of a paraffin-type MPCM in mixtures of bitumen mastics to prevent rutting. The studied mastic of bitumen and cement and mastic of bitumen, cement, and MPCM. Multiple stress creep recovery (MSCR) test parameters of stress levels (0-256 kPa) and recovery time (9-40 s) are investigated to determine rheology properties (Jnr and percentage recovery) of the mastics. Performance grade (PG) temperature sweep tests (40°C-80°C) are performed to evaluate complex modulus and phase angle of the mastics G*/sin(θ). The results show that the presence of MPCM in the mastics leads to higher Jnr values and lower percentage of recoveries compared to those using only cement as the filler. Higher Jnr values indicate lower stiffness of the mastics. This result is also confirmed by the results of the temperature sweep tests. At 75% MPCM, the stiffness of the mastic is at the same level as that of pure bitumen. At higher temperatures, pure bitumen and all mastics become less viscous, while the presence of MPCM shows nonlinearity in the range of 40°C-50°C. This temperature range is apparently around the phase change temperature of the MPCM. The MSCR test also shows that at 40°C, mastics containing 50% MPCM or less have a complete elastic recovery, shown by their constant Jnr values. At 60°C, all mastics have lower Jnr values compared to the pure bitumen sample. Hence, it is expected that the presence of MPCM, while reducing temperature variations, does not jeopardize the rutting resistance of the pavement. © 2021 American Society of Civil Engineers.